(untitled) (Innovative professional education, 2024)
The subsection considers aspects related to improving the quality of pedagogical activity of teachers of general education disciplines in vocational education institutions. It highlights the features of modern general education of students, analyses the state of vocational education, the content of the Model Educational Programme, educational losses, and PISA results. The conclusion is made about the need for systematic development of professional competence of teachers of general education disciplines.